Effects of Geometer’s Sketchpad on Algebraic Reasoning Competency amongst Students in Malaysia - Li, Hwa Li; Zulnaidi, Hutkemri (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This study investigates the impact of incorporating Geometer's Sketchpad into GSP-based instruction on the algebraic reasoning proficiency of students. The research outlines the application of GSP-based instruction, utilizing Geometer's Sketchpad in Mathematics education, with a specific focus on solving quadratic problems. A quasi-experimental design, involving non-equivalent pre-test and post-test assessments, was conducted on 60 second-grade students at a private secondary school in Kuala Lumpur. The experimental group, consisting of 30 students, utilized Geometer's Sketchpad in their learning, while the control group, comprising 30 students, received traditional instruction. Data analysis was performed using ANATES 4 and SPSS 25.0 software, incorporating inferential statistics such as paired t-tests and one-way ANCOVA for quantitative data analysis. Both groups underwent an initial pre-test assessment. The research findings reveal a significant disparity in algebraic reasoning proficiency between the two groups, indicating substantial improvement after the intervention. Consequently, the integration of Geometer's Sketchpad in GSP-based instruction contributed to the enhancement of students' algebraic reasoning skills, particularly in quadratic problem-solving. In conclusion, this study underscores the potential of Geometer's Sketchpad as an instructional intervention, urging mathematics educators to contemplate its incorporation as an alternative teaching tool.